Effect of Early Rehabilitation and Nursing Intervention on the Rehabilitation Prognosis of Elderly Stroke Hemiplegia Patients in the Department of Neurology - Min Ning; Fang Chen; Hui Wu; Haihua Zheng; Chunmei Zheng; Shufen Li (Applied Bionics and Biomechanics)
Objective. To explore the influence of rehabilitation outcomes in older patients with stroke hemiplegia from the neurology department by early rehabilitation nursing. Methods. 70 cases of old patients with stroke hemiplegia from 2020/01 to 2021/01 were randomly divided into observation group (35 cases) and control group (35 cases). The control group was nursed by usual care. The observation group was nursed by early rehabilitation nursing. Nursing efficacy was observed. Results. The scores of active demand, resistance, and rehabilitation nursing cooperation degree after the nursing for the observation group were higher than the control group (P<005). The score of NIHSS after the nursing for the observation group was lower than that for the control group (P<005). The scores of BI, BBS, and Fugl-Meyer after the nursing for the observation group were higher than those for the control group (P<005). The total rate of nursing satisfaction for the observation group was higher than the control group (P<005). Conclusion. Early rehabilitation nursing can improve rehabilitation initiatives, rehabilitation outcomes, and nursing satisfaction in older patients with stroke hemiplegia from the neurology department.